Design of wideband tonpilz transducers for underwater SONAR applications with finite element model. (1st December 2021) - Abdullah, Zeeshan; Naz, Sidra; Raja, Muhammad Asif Zahoor; Zameer, Aneela
Abstract: This paper describes the designing and optimization of tonpilz type transducers based on number of layers, width and thicknesses and type of active materials, dimensions of head and tail mass by exploiting finite element models for their effective and optimized usage in underwater SONAR applications. Geometry parameters of tonpilz transducers have been studied in terms of active piezoelectric stack and associated components comprised of head and tail masses and optimized structure is explored. Piezoelectric stack including piezoceramic material (PZT-4) and single crystal (PMNPT), is utilized for underwater acoustic generation, while Aluminum is taken as head mass and highly attenuated material stainless steel is used for tail mass. Performance of tonpilz transducer has been investigated and evaluated in terms of total radiating power (TRP), transmitting voltage response (TVR), directivity index and specific acoustic impedance for all designed structures. Comparison is carried out for the optimized structure that provides high sensitive frequency region in form of constant TVR and maximum sound directivity used for accurate under water detection applications. TVR in the sensitive region using PMNPT as the stack material shows enhanced results as compared to PZT-4. Sound intensity level in terms of TRP peaks also rises with a greater number of layers for both PMNPT and PZT-4 driving stack materials. Furthermore, it has been observed that Driving stack material is more effective than the other components of Tonpilz transducer because it effects the flat response and also enhances the TVR response. Secondly, head mass of the Tonpilz transducer is more effective than the remaining because resonance and flexural frequency depend on it.